Realtime analysis and well planning using wireline logs in a hydrogeological context. Issue 1 (1st December 2019) - Birt, Benjamin; Filiptsova, Olga; Ryan, Sheryl; Hopper, Tim
Summary: During the drilling process, numerous decisions must be made, often with limited information. In a known area prior knowledge often guides these decisions. In a recent drilling program in the Northern Perth Basin, as part of a research project to monitor the use of aquifers, petrophysical logs were used to help inform some critical decisions. Further analysis of the data collected from the borehole was going to be used to monitor quality, extent and connectivity of the numerous aquifers that make up the Northern Perth Basin. As an aquifer monitoring program, it is critical to ensure that the bore is accessing the aquifer in question. Therefore, accurate knowledge of depth and quality of formation is key. This paper shows how to use a simple set of petrophysical logs including natural gamma, resistivity and borehole magnetic resonance logs can be used to make informed decisions. For example, using a composite log, decisions were able to be made on screen placement prior to running, and also helped decide if extra bores on the same drilling pad were required. Finally, we were able to determine the salinity of ground water from wireline logs. The ability to make these decisions with accurate information not only ensures successful well completion but also maximises resource use.